Immunopathogenesis of Juvenile Systemic Sclerosis - Stevens, Anne M.; Torok, Kathryn S.; Li, Suzanne C.; Taber, Sarah F.; Lu, Theresa T.; Zulian, Francesco (Frontiers in Immunology, 2019)
Juvenile-onset systemic sclerosis (jSSc) is a rare and severe autoimmune disease with associated life-threatening organ inflammation and evidence of fibrosis. The organ manifestations of jSSc resemble adult SSc, but with better outcomes and survival. The etiology of jSSc appears treflect adult-onset SSc, with similar inflammatory mediators and autoantibodies, but with a significant population of children with uncharacterized anti-nuclear antibodies. The genetics of patients with jSSc differ from women with SSc, resembling instead the genes of adult males with SSc, with additional HLA genes uniquely associated with childhood-onset disease. Current treatments are aimed at inhibiting the inflammatory aspect of disease, but important mechanisms of fibrosis regulated by dermal white adipose tissue dendritic cells may provide an avenue for targeting and potentially reversing the fibrotic stage.